2014
DOI: 10.1063/1.4880659
|View full text |Cite
|
Sign up to set email alerts
|

Extreme waves induced by strong depth transitions: Fully nonlinear results

Abstract: Articles you may be interested in Mechanical energy dissipation induced by sloshing and wave breaking in a fully coupled angular motion system. I. Theoretical formulation and numerical investigation Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 17 publications
8
51
0
Order By: Relevance
“…Fortunately, the optical measurements allow us to extract statistical information continuously in space, rather than at a discrete set of positions. This capability is crucial for identifying regions of anomalous activity, as previous studies have suggested such regions to be highly localized [31]. While examining the complete distribution of η at a continuum of positions would prove impractical, the first few statistical moments provide useful proxies.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the optical measurements allow us to extract statistical information continuously in space, rather than at a discrete set of positions. This capability is crucial for identifying regions of anomalous activity, as previous studies have suggested such regions to be highly localized [31]. While examining the complete distribution of η at a continuum of positions would prove impractical, the first few statistical moments provide useful proxies.…”
Section: Resultsmentioning
confidence: 99%
“…The computational domain becomes a uniform flat strip, more amenable to computations. A similar conformal mapping formulation has been used by Viotti et al, 6,7 but their underlying current is irrotational. In Viotti et al, 6 two examples are considered.…”
Section: Introductionmentioning
confidence: 99%
“…And finally an example with one supercritical stationary wave generation, due to the presence of a submerged triangular obstacle. In Viotti and Dias, 7 an initial random wave field is given and allowed to propagate toward a long shallower region, allowing for extreme wave formation. The scope of these interesting studies is different from ours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid domain of each patch measures eight and three ship lengths in the x and y directions, respectively. Numerical beach as introduced in Viotti & Dias [45] is located at the downstream edge (negative x direction) of each patch, and the ship waves approaching downstream boundary are gradually damped and eventually eliminated. Moreover, in all computational cases, Hull 2 starts at the initial position of st/L = −3, and the overtaking process ends with st/L = 1.5.…”
Section: (B) Time-marching By Moving-patch Methodsmentioning
confidence: 99%